Managing aflatoxin in smallholder groundnut production in Southern Africa: Paired comparison of the windrow and Mandela cock techniques. (October 2018) - Matumba, Limbikani; Singano, Lazarus; Tran, Bruno; Mukanga, Mweshi; Makwenda, Beatrice; Kumwenda, Wycliffe; Mgwira, Sharif; Phiri, Sam; Mataya, Frazer; Mthunzi, Talentus; Alfred, Sharon; Madzivhandila, Tshilidzi; et al.
Abstract: Timely drying of groundnuts is important after harvest. In most parts of sub-Saharan Africa, moisture content reduction is practically achieved by solar drying. In particular, the groundnuts are traditionally cured in the field using the inverted windrow drying technique. Recently, the Mandela cock technique, a ventilated stack of groundnut plants with a chimney at the center, has been introduced in the southern Africa region with the aim of reducing moisture content and the risk of aflatoxin contamination. An on-farm study was conducted in Malawi to compare the effectiveness of the Mandela cock and Windrow drying techniques with respect to aflatoxin control. For two consecutive years, farmers (2016, n = 29; 2017; n = 26) were recruited to test each of the two drying techniques. A mixed-design ANOVA showed that the Mandela cock groundnut drying technique led to significantly (p < 0.001) higher aflatoxin levels in groundnut seed compared to the traditional inverted windrow drying (5.7 μg/kg, geometric mean vs 2.5 μg/kg in 2016 and 37.6 μg/kg vs 8.4 μg/kg in 2017). The present findings clearly demonstrate the need for regulation and technology validation if farmers and consumers are to benefit. Highlights: Mandela cock drying of groundnuts was compared against inverted windrow in terms of aflatoxin. Mandela cock is not superior to inverted windrow technique. In 33.6% of the aflatoxin positive groundnut samples, aflatoxin G1 (AFG1 ) > AFB1 .